Educational Administration According to the Principles of Cakka - เงาสงค์, พระมหาหล่อ ฐานุตฺตโร (Journal of Educational Review Faculty of Education in MCU, 2018)
This article is intended to describe the administration in educational institutions with quality. Buddhist principles are applied to achieve the goal and facilitate administrators in doing their duty well. The administration is an art and the success of work depends on others. Therefore, administrators have to apply the Buddhist principles in their administration appropriately. The Buddhist principles appropriate to educational administration are the four principles of Cakka; 1. Living in a suitable region, 2.Association with good people, 3.Setting oneself in the right course, and 4.Having formerly done meritorious deeds.